Strategies to identify and overcome misunderstandings about Behavior Analysis: a Literature Review (Brazilian Journal of Behavioral and Cognitive Therapy, 2023)
This is a review of studies on the misunderstandings of Behavior Analysis and the procedures for teaching this area. Fifteen studies were selected from the PsycInfo, PubMed and BVS databases, Sobre Comportamento e Cognição and Comportamento em Foco collections and added two studies. The studies analyzed showed: 1) the use mainly of questionnaires to assess the knowledge of different audiences about Behavior Analysis and 2) the existence of imprecise concepts in teaching materials to train psychologists and pedagogues and in the national popular media. Studies were also found that successfully taught the concepts of Behavior Analysis to people from other areas who can benefit from behavioral technology in their professional practice. It is concluded that it is necessary to program contingencies that favor an accurate dissemination of Behavior Analysis, aiming to overcome prejudices and misunderstandings about this area.
Keywords: Behavior Analysis; Teaching Behavior Analysis; Prejudices; Misunderstandings